‘Our place under the sun’: survivor-centred approaches to children born of wartime sexual violence - Rodríguez Di Eugenio, Alessia (Human rights review, 2021)
Children ‘born of war’ refer to people of any age conceived as the result of sexual violence at the hands of armed forces or groups during war, displacement, genocide or military occupation. Due to the circumstances of their birth, children ‘born of war’ can experience social stigma, discrimination and exclusion, resulting in diminished life chances and opportunities. At the same time, children ‘born of war’ fall through the cracks of global policy frameworks. In this article, we explore the reasons for this, arguing that the nature of the harm these children endure renders their status as a victim group elusive. We propose a survivor-centred approach drawing on the lived experiences of children ‘born of war’. The approach recognizes the agency of children and draws attention to their expressed desire to contribute to, and participate in, processes of social reconstruction and reconciliation.